Wastewater nitrogen budgets can be resolved by complementary functional gene and physicochemical methods. (June 2019) - Rose, A.; Munksgaard, N.; Kaestli, M.; Bodrossy, L.; van de Kamp, J.; Tsoukalis, S.; Gibb, K.
Abstract: A nitrogen budget for wastewater stabilisation ponds in tropical northern Australia indicated a deficit between influent and effluent Total Nitrogen of ≈46.5%. Stable nitrogen isotope ratios in pond waters and gas emission measurements showed that the deficit was a result of loss of mainly dinitrogen gas while emissions of nitrous oxide and ammonia were minor. We explored spatial and temporal patterns of nitrogen cycling across the pond system by analysing diversity and function of denitrification ( nosZ ) and Anammox ( hzsA ) genes known to be responsible for nitrogen gas emission. The relative gene abundance and activity supported the physicochemical evidence that the budgetary nitrogen deficit was largely due to dinitrogen gas emission. Contrary to expectation, most of the dinitrogen gas emissions appeared to occur after the first facultative pond despite nosZ genes being abundant and active. This suggests that other barriers to effective denitrification existed in the facultative pond. The dominant abundance and activity of hzsA genes in the final maturation pond indicated that dinitrogen gas emissions from this pond were likely associated with the Anammox process.